Advanced cicatricial retinopathy of prematurity–outcome and complications. Issue 4 (April 1996) - Knight-Nanan, D M; Algawi, K; Bowell, R; O'Keefe, M
Abstract : AIMS: To assess the outcome and complications of patients with advanced retinopathy of prematurity (ROP). METHODS: All patients with eyes achieving stage 4 or 5 retinopathy of prematurity were reviewed. Twenty one eyes were diagnosed during ROP screening in maternity hospitals and 10 eyes were of infants transferred for treatment. RESULTS: Thirty one eyes of 17 patients were included. Thirteen eyes were treated for acute disease but progressed to stage 4 or 5; seven had cryotherapy and six diode laser photocoagulation. Cataract was found in 17 eyes (54.8%), glaucoma in seven eyes (22.6%), microphthalmos in 15 (48.4%), and corneal opacification in four eyes (12.9%). Fifteen eyes had surgical procedures; two (6.5%) had trabeculectomy, four (12.9%) had lensectomy, and nine (29%) retinal detachment repair. Transferred infants had their initial eye examination later than infants in hospitals screened by the authors and 80% of them had progressed beyond threshold ROP by the time they were transferred for treatment. Twenty nine eyes (93.6%) had visual acuities of 3/60 or less and only two eyes (6.5%) achieved 6/18 or less. CONCLUSION: The visual outcome of the eyes undergoing retinal re-attachment surgery was disappointing. Cataract, microphthalmos, and glaucoma were the most frequent complications, and surgical intervention was often required. The need for children who are blind as a result of ROP to have long term follow up is shown.